Cover Feature: Fe, N‐Codoped Graphdiyne Displaying Efficient Oxygen Reduction Reaction Activity (ChemSusChem 1/2019). Issue 1 (27th December 2018) - Si, Wenyan; Yang, Ze; Wang, Xin; Lv, Qing; Zhao, Fuhua; Li, Xiaodong; He, Jianjiang; Long, Yunze; Gao, Juan; Huang, Changshui
Abstract : The Cover Feature shows an efficient non‐precious‐metal electrocatalyst for oxygen reduction reaction (ORR). In their Communication, W. Y. Si et al. demonstrate that the Fe‐N co‐doped graphdiyne (Fe‐N‐GDY) performed excellent catalytic activity in both alkaline and acidic media, comparable to commercial Pt/C. Moreover, the stability and methanol tolerance of Fe‐N‐GDY are better than those of Pt/C. The powerful synergistic effect between Fe, N and GDY plays a critical role in improving the activity and stability of Fe‐N‐GDY. More information can be found in the Communication by W. Y. Si et al. onpage 173 in Issue 1, 2019 (DOI:10.1002/cssc.201802170 ).